A systematic review of impacts of COVID-19 on depression and anxiety among general populations around the world - Hou, Jianbo; Duan, Wenjie; Wang, Yuqian; Liao, Yujing; Bu, He; Mu, Wenlong; Tang, Xiaoqing; Liu, Dong (Frontiers in Public Health, 2025)
BackgroundThe COVID-19 pandemic has profoundly impacted global mental health, with significant disparities in depression and anxiety observed across populations and countries. Existing literature highlights the role of social determinants of health (SDH) in shaping mental health outcomes, yet systematic reviews synthesizing these impacts across diverse socioeconomic and policy contexts remain limited. This study provides an overview of how COVID-19 is affecting depression and anxiety among general populations, alongside inequalities driven by the SDH.MethodsSix databases (CNKI, Embase, PubMed, Scopus, Cochrane Library, Web of Science) were searched from March 2020 to February 2024. Inclusion criteria encompassed cross-sectional/longitudinal studies assessing depression/anxiety in adults (≥18 years) using validated scales (e.g., PHQ-9, GAD-7). After screening 4,916 records, 59 studies met eligibility criteria. Quality assessment utilized the Joanna Briggs Institute tool, and data extraction covered study characteristics, outcomes, and SDH factors. This review is registered with PROSPERO: CRD420251023201.ResultsAmong 59 studies (39 from low- and middle-income countries [LMICs]; 16 from high-income countries [HICs]), younger individuals, women, and socioeconomically disadvantaged groups exhibited heightened vulnerability to depression and anxiety. High-income countries with stringent lockdowns (e.g., the U.S., France) reported sustained psychological distress, while nations adopting effective early containment strategies saw mental health improvements over time. Population-level determinants, including healthcare infrastructure and policy stringency, significantly influenced outcomes. Low-resource settings faced worsened mental health burdens due to prolonged restrictions and limited medical access. Individual and community-level factors such as unemployment, housing instability, and low social support amplified risks. Temporal trends revealed worsening mental health during extended lockdowns and disparities in recovery trajectories across regions.ConclusionThe COVID-19 pandemic exacerbated mental health inequalities, disproportionately affecting specific groups and underscoring the interplay of SDH. Tailored interventions addressing socioeconomic vulnerabilities, enhancing social support, and balancing infection control with psychological well-being are critical.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251023201, identifier CRD420251023201